Development Device Learning Differentiated with Use PJBL Method on Material Get up Flat - Juan Gabriel Mongkau; Juliana Margareta Sumilat; Richard DH Pangkey (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research aims to develop a mathematics teaching module based on differentiated learning integrated with the Project-Based Learning (PjBL) method, specifically for the topic of spatial structures (